2009
DOI: 10.1161/hypertensionaha.109.138818
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin Is a Critical Regulator of Cardiac Hypertrophy in Spontaneously Hypertensive Rats

Abstract: Abstract-Evidence exists that protein kinase C and the mammalian target of rapamycin are important regulators of cardiac hypertrophy. We examined the contribution of these signaling kinases to cardiac growth in spontaneously hypertensive rats (SHRs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 44 publications
5
73
0
Order By: Relevance
“…These data suggest that the cardiac hypertrophy in Acsl1 TϪ/Ϫ mice was mediated by activation of the mTOR pathway. Possible causes of enhanced mTOR signaling include elevations in amino acid availability (2), enhanced glycolytic flux (41), elevated plasma insulin (21), and hypertension (42). mTOR activation in Acsl1 TϪ/Ϫ hearts probably resulted from a combination of several of these factors, including the 32% higher amino acid content and the increase in glucose uptake and glycolysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggest that the cardiac hypertrophy in Acsl1 TϪ/Ϫ mice was mediated by activation of the mTOR pathway. Possible causes of enhanced mTOR signaling include elevations in amino acid availability (2), enhanced glycolytic flux (41), elevated plasma insulin (21), and hypertension (42). mTOR activation in Acsl1 TϪ/Ϫ hearts probably resulted from a combination of several of these factors, including the 32% higher amino acid content and the increase in glucose uptake and glycolysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Activated mTOR is present in several models of cardiac hypertrophy and is likely to be an important signal in the pathway that mediates hypertrophy. For example, S6K phosphorylation is increased in the hypertrophied hearts of spontaneous hypertensive rats (SHR), and treatment with the mTOR inhibitor rapamycin attenuates the hypertrophy without altering the hypertension (42). Similarly, rapamycin inhibits thyroid hormone-induced S6K phosphorylation and cardiac hypertrophy (25).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it also has been used for other purposes, both in animal models and humans. For example, previous studies have demonstrated its efficacy in the treatment of cardiac hypertrophy in spontaneously hypertensive rats (99) and in reducing pressure overload-induced hypertrophy in mice (91,100). Rapamycin also has proven beneficial for treatment of polycystic kidney disease in mice (101,102), a therapy that has moved to clinical trials (103,104), and a rapamycin analog is now approved for the treatment of renal cancer (105).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] However, other studies have challenged the importance of mTOR-mediated protein synthesis and growth. For example, deletion of the ribosomal S6 kinases, direct downstream effectors of mTOR, did not attenuate pathological, physiological, or insulin-like growth factor receptor-induced cardiac hypertrophy.…”
Section: Clinical Perspective On P 1082mentioning
confidence: 99%